Adenosine A2b receptors control A1 receptor‐mediated inhibition of synaptic transmission in the mouse hippocampus. (19th February 2015) - Gonçalves, Francisco Q.; Pires, Johny; Pliassova, Anna; Beleza, Rui; Lemos, Cristina; Marques, Joana M.; Rodrigues, Ricardo J.; Canas, Paula M.; Köfalvi, Attila; Cunha, Rodrigo A.; Rial, Daniel
Abstract: Adenosine is a neuromodulator mostly acting through A1 (inhibitory) and A2A (excitatory) receptors in the brain. A2B receptors (A2 B R) are Gs/q ‐protein‐coupled receptors with low expression in the brain. As A2 B R function is largely unknown, we have now explored their role in the mouse hippocampus. We performed electrophysiological extracellular recordings in mouse hippocampal slices, and immunological analysis of nerve terminals and glutamate release in hippocampal slices and synaptosomes. Additionally, A2 B R‐knockout (A2 B R‐KO) and C57/BL6 mice were submitted to a behavioural test battery (open field, elevated plus‐maze, Y‐maze). The A2 B R agonist BAY60‐6583 (300 nm ) decreased the paired‐pulse stimulation ratio, an effect prevented by the A2 B R antagonist MRS 1754 (200 nM) and abrogated in A2 B R‐KO mice. Accordingly, A2 B R immunoreactivity was present in 73 ± 5% of glutamatergic nerve terminals, i.e. those immunopositive for vesicular glutamate transporters. Furthermore, BAY 60‐6583 attenuated the A1 R control of synaptic transmission, both the A1 R inhibition caused by 2‐chloroadenosine (0.1–1 μm ) and the disinhibition caused by the A1 R antagonist DPCPX (100 nm ), both effects prevented by MRS 1754 and abrogated in A2 B R‐KO mice. BAY 60‐6583 decreased glutamate release in slices and also attenuated the A1 R inhibition (CPA 100 nm ). A2 B R‐KO mice displayed a modified exploratory behaviour with an increased time in the central areas of the open field, elevated plus‐maze and the Y‐maze and no alteration of locomotion, anxiety or working memory. We conclude that A2 B R are present in hippocampal glutamatergic terminals where they counteract the predominant A1 R‐mediated inhibition of synaptic transmission, impacting on exploratory behaviour. Abstract : Adenosine is well described as a neuromodulator in the central nervous system acting through A1R to control synaptic transmission. This study provides the first direct demonstration that, in the mouse hippocampus, the inhibition of synaptic transmission operated by A1R activation, can be influenced by A2B R activation through a mechanism to be clarified. The activation of these synaptic A2B R decrease the functioning of the predominant A1 R‐mediated inhibition of synaptic transmission, suggesting a primary fine‐tuning role for synaptic A2B R modifying the exploratory behavior, which is dependent on A1 R activation.